Negotiating Destiny and Human Agency in Islamic Popular Culture: A Hermeneutic Reading of Negeri 5 Menara - Khoirul Anwar Syarifuddin; Syukron Affani; Afifullah; Qurroh A'yuniyah; Inayatur Romaniyatul M. (KALAM, 2026)
Studies of destiny (qadar) and human agency (ikhtiar) in Islam have largely focused on the interpretation of religious texts, while their representation in popular culture and visual media has received limited scholarly attention. This article examines how the Indonesian Islamic film Negeri 5 Menara represents the relationship between divine destiny and human effort within contemporary Muslim popular culture. Employing a qualitative hermeneutic approach, the study analyzes the film through Hans-Georg Gadamer’s concept of fusion of horizons and Fazlur Rahman’s double movement theory. The findings reveal that the film portrays human effort as a moral responsibility that operates within the framework of divine sovereignty. Through the values of discipline, perseverance, and the motto man jadda wajada, the narrative emphasizes active human agency while simultaneously acknowledging the limitations imposed by God’s will. The analysis further identifies three interconnected dimensions of Qur’anic agency: ethical responsibility, ontological dependence on divine authority, and teleological orientation through tawakkul. These dimensions are articulated through the integration of Islamic spirituality, pesantren values, and aspirations for global achievement. This study contributes to the expansion of Qur’anic reception studies into the field of visual media and offers a new perspective on how Islamic popular culture mediates the negotiation between religious values and Muslim modernity in contemporary society. [Kajian tentang takdir dan ikhtiar dalam Islam selama ini lebih banyak berfokus pada penafsiran teks-teks keagamaan, sementara representasinya dalam budaya populer dan media visual masih relatif terbatas. Artikel ini mengkaji bagaimana film Islam Indonesia Negeri 5 Menara merepresentasikan hubungan antara takdir Ilahi dan usaha manusia dalam konteks budaya populer Muslim kontemporer. Penelitian ini menggunakan pendekatan hermeneutik kualitatif dengan memanfaatkan konsep fusion of horizons Hans-Georg Gadamer dan teori double movement Fazlur Rahman. Hasil penelitian menunjukkan bahwa film tersebut menggambarkan usaha manusia sebagai tanggung jawab moral yang berlangsung dalam bingkai kedaulatan Tuhan. Melalui nilai-nilai disiplin, kerja keras, dan motto man jadda wajada, narasi film menegaskan pentingnya agensi manusia yang aktif sekaligus mengakui keterbatasan manusia di hadapan kehendak Ilahi. Analisis ini juga mengidentifikasi tiga dimensi agensi Qur’ani yang saling berkaitan, yaitu tanggung jawab etis, ketergantungan ontologis kepada Tuhan, dan orientasi teleologis melalui sikap tawakal. Ketiga dimensi tersebut direpresentasikan melalui perpaduan spiritualitas Islam, nilai-nilai pesantren, dan aspirasi untuk meraih keberhasilan global. Penelitian ini berkontribusi pada perluasan kajian resepsi Al-Qur’an ke ranah media visual serta menawarkan perspektif baru mengenai bagaimana budaya populer Islam menjadi ruang negosiasi antara nilai-nilai keagamaan dan modernitas Muslim dalam masyarakat kontemporer.]